Variational Approach to Damage Induced by Drainage in Partially Saturated Granular Geomaterials - Ommi, Siddhartha H.; Sciarra, Giulio; Kotronis, Panagiotis (Frontiers in Mechanical Engineering, 2022)
Within the context of immiscible bi-phasic flow in porous media, when the non-wetting fluid invades the pore spaces which are a priori saturated with the wetting fluid, capillary forces dominate if the pore network is formed by fine-grained soils. Owing to the cohesion-less frictional behavior of such soils a capillary force-driven fracturing phenomenon has been put forward by some researchers. Unlike the purely mechanistic tensile force-driven mode-I fracturing that typically has been attributed to the formation of desiccation cracks in soils, attempts to model this alternate capillarity-driven mechanism have not yet been realized at a continuum scale. However, the macro-scale counterpart of the capillary energy associated with the various pore-scale menisci is well established as the interfacial energy characterized by the soil-water retention curve. An investigation of the possible contribution of this interfacial energy in supplying the dissipation related to fracture initiation is the essence of this work, inspired by the vast literature on gradient damage modeling.